Studi In Sillico Gen CTX-M15 sebagai Biomarker Escherichia coli ESBL - Ayanti, Bio Putri; Adhipurna, Novian; Novita, Iswiyanti; Prihandini, Yustin Ari (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Escherichia coli is most common nosocomial pathogenic bacteria recognized as the highest cause of ESBL production. Derivatives of CTX-M, especially type CTX-M-15 (blaCTX-M-15) as the dominant ESBL-encoding gene found among E. coli isolates. The most important component in PCR is primer. Primer design can be done by in silico bioinformatics analysis. This study was conducted to produce a primer sequence of E. coli CTX-M-15 gene as a candidate biomarker for E. coli ESBL detection. The method used was in sillico observational using the Primer3Plus application and in silico PCR on candidate primers for the E. coli CTX-M-15 gene. Primers were selected based on criteria including%GC, primer length, Tm (melting temperature), stability, and primer interactions (the presence of dimers and hairpins). The sample used was the nucleotide sequence of the E. coli CTX-M-15 gene strain K-20 plasmid Genbank: GQ330540.1. The results showed that 2 pairs of forward and reverse primer pairs (pairs 1 and pairs 5) were able to amplify the blaCTX-M-15 gene sequence measuring 525bp and 519bp. In silico PCR analysis resulted in 2 pairs of new primer pairs being successfully designed and potentially used as DNA biomarkers from Escherichia coli in early and rapid detection of ESBL infection.